An axisymmetric inclusion in one of two perfectly bonded dissimilar elastic half-spaces - Korsunsky, A (American Society of Mechanical Engineers, 1997)
This paper introduces an effective method for the solution of axisymmetric elastic inclusions in bonded dissimilar half-spaces. The method leads to new concise expressions for the elastic fields in terms of only two scalar Papkovich potential functions. A host of earlier solutions, which were obtained using a range of alternative techniques, involving surface stress relaxation and Hankel transforms, are shown to be subsumed in the present result.